The Infinitude of Prime Numbers Revisited - Chowdhury, Munibur Rahman (GANIT: Journal of Bangladesh Mathematical Society, 2018)
We present here a proof of the infinitude of prime numbers based on the sequence n! + k, k = 2, 3, …, n. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 185-187